Moonglow - Callihan, Kristen (Callihan, Kristen. Darkest London series, 2012)
Newly widowed, Daisy Craigmore decides to lead a life of debauchery until the discovery of a dead body leads her to Ian, a werewolf who tempts her like no other, and as they investigate this strange case, they must decide just how much they are wiling to risk for love.